أثر الترقية على المسار المهني في المنظمة - وراس، أمنية (جامعة وهران2 محمد بن أحمد, 2021)
يندرج موضوع الترقية ضمن المواضيع التي ترتبط بالعنصر البشري والتي تلعب دورا أساسيا في زيادة رضاه المهني، كونها تمثل العمود الفقري في مسار حياته المهنية، فهي إحدى السياسات الرئيسية التي تؤثر على إدارة الموارد البشرية، لذا تكتسي أهمية بالغة بالنسبة للفرد وللمنظمة على حد سواء، ووسيلة من الوسائل التي تدفع العاملين للتنمية الذاتية، وأحد الحوافز لزيادة رضاهم المهني. وعليه، فإن هذا البحث سيتناول قضية ذات أهمية بالغة حيث أنها تعني البناء الإداري والتنظيمي لمختلف المؤسسات باختلاف نوع النشاط الممارس، وهذا باعتبارها ترتبط ارتباطا مباشرا بالعامل وبوضعه ومكانته في المؤسسة. ومنه يهدف هذا البحث إلى محاولة الكشف عن مدى إمكانية اعتبار الترقية كأحد العوامل الدافعة بالعاملين للسعي لتطوير حياتهم المهنية على مستوى أي تنظيم كان.
Promotion is a one of the topics related to the human element that plays a key role in increasing his professional satisfaction; being the backbone of his managerial career, it is one of the main policies affecting human resources management; therefore it is of paramount importance for both the individual and the organization and one of the means that drive workers to self-development and one of the incentives to increase their professional satisfaction. This research treats an issue of great importance as it concerns the administrative and organizational structure of different organizations with different types of activities, as it is directly related to the worker and his position in the organization. The aim of this study is to verify the possibility of considering the promotion as a factor driving the workers to develop their professional career at in the organization
Keywords: إدارة المنظمات -- منظمات الأعمال -- إدارة الموارد البشرية -- التنمية المهنية -- الرضا الوظيفي